On total edge irregularity strength of polar grid graph. Issue 1 (11th December 2019) - Salama, F.
Abstract: For a graph G, an edge irregular total r -labelling π : V ∪ E → { 1, 2, 3, …, r } is a labelling for edges and vertices of a graph G in such a way that the weights of any two different edges are distinct. The minimum for which G admits an edge irregular total r -labelling is called total edge irregularity strength of G, t e s ( G ) . In this paper, the exact value of total edge irregularity strength of the polar grid graph was determined. We have also determined the total edge irregularity strength for a polar grid graph.